Pemeliharaan Perilaku Hidup Bersih dan Sehat Sebagai Upaya Peningkatan Kesehatan Pribadi Guru PJOK Kabupaten Lamongan - Kaharina, Arifah; Wahjuni, Endang Sri; Hidayat, Taufiq; Andrijanto, Dony (Universitas Negeri Surabaya, 2023)
This community service is carried out in Lamongan Regency with the aim that the incidence of Covid-19 at the beginning of the pandemic is quite high, and in 2022 it has succeeded in being at PPKM level1, so it needs the support of all community residents including school residents to continue to increase understanding and awareness of the need for healthy living by implementing PHBS. Based on this situation, the community service program with PJOK teacher partners in Lamongan Regency through socialization and training activities is related to the implementation of a clean lifestyle. PJOK teachers are given knowledge about clean and healthy lifestyles and their application in daily life in socialization activities. And trained to make hand sanitizers with materials that are easy to get and low cost in training activities, so that they can be applied in schools.